Kuat Tekan Bebas Tanah Lempung Bukit Rawi Distabilisasi Pasir dan Semen - Anwar Muda (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
Bukit Rawi clay soil properties only have a value of UCS at 0:41 kg/cm2 so it does not meet the technical requirements Lapis Foundation Under Highway. To that end, will be improved with the addition of sand and cement and is expected to meet the technical requirements highway pavement. The aim of this study was to determine how much the addition of sand and cement on clay soil stabilization Bukit Rawi for pavement highway. The results showed that after the addition of 12% sand with cement 2%, the value of UCS rose to 0:49 kg/cm2 of initial conditions 0:41 kg/cm2. Then, the addition of 4% cement, UCS value also increased by 4:44 kg/cm2. At addition of cement amounted to 6%, the value of UCS has increased to 5:29 kg/cm2 and the addition of cement amounted to 8%, the value of UCS rose to 7:33 kg/cm2 and the addition of cement 10%, the value of UCS increased to 9:06 kg/cm2. So that, with the addition of sand by 12% and 8% of cement optimum technically qualified foundation layer under the highway because of the value of UCS result 7:33 kg/cm2> 7:33 kg/cm2.